AOFAS and Karlsson-Peterson scales in evaluating patients treated with modified Broström-Gould and suture tape augmentation for ankle instability: a performance analysis - Hugo B. Torrano-Orduña; Ana C. King-Martinez; Alberto Cuellar-Avaroma; V. Jonathan Ramirez-Gomez; Rafael Ortega-Orozco; Diego A. de Zulueta-Ortiz; Luis A. Gómez-Carlín (Journal of the Foot & Ankle, 2022)
Objective: The objective of this study was to evaluate the performance of the American Orthopedic Foot and Ankle Society (AOFAS) and Karlsson-Peterson scales in patients with lateral ankle instability treated with modified Bröstrom-Gould (MBG) plasty and suture tape augmentation. Methods: This retrospective, bicentric, cohort study involved consecutive patients with lateral ankle instability treated with MBG plasty and suture tape augmentation. The Visual Analog Scale (VAS), AOFAS scale, and Karlsson-Peterson scale were used in pre-/postoperative assessments. Results: Fifty-five patients who underwent MBG plasty and suture tape augmentation were included. Mean preoperative and postoperative VAS scores were 7.1 ± 1.4 and 1.3 ± 1.6 (p<0.001), respectively. Mean AOFAS scores were 61.3 ± 21.1 and 95.4 ± 8.4, respectively (p<0.001). Mean Karlsson-Peterson scale scores were 46.8 ± v14.3 and 95.2 ± v7.9 (p<0.001), respectively. Conclusions: The Karlsson-Peterson scale showed a better performance than the AOFAS scale in the clinical and functional evaluation of patients with ankle instability treated with MBG plasty and suture tape augmentation. Level of Evidence III; Therapeutic Studies; Comparative Retrospective Study.